The Public Service Ethics in Bali in The Bureaucratic Reform Era - Adi Sastra Wijaya (Journal of Public Administration and Local Governance, 2018)
Abstract This article describes the performance of the public servants, namely the bureaucracy in serving the public in Bali. The main problem proposed in this article is how the public servants in Bali in the bureaucratic reform era are and what ethic underlies the running of this service. The data were collected through the interviews, observation, and documentation. Data analysis was done by the public service theory. The results of the study present that the public services in Bali are strongly influenced by Hinduism culture especially the spirit of Sewaka Dharma manifested in the government bureaucrats. The concept of Sewaka Dharma is in line with the values echoed in the bureaucratic reform. It contains the values and concepts related to the service to others and the accountability to God. Keywords: Ethic; Public Servants; Bureaucratic Reform; Bali